Project-Based Learning for Integrating Creative Responsibility and Creative Product Development in Pre-Service Physics Teacher - Suyidno, Suyidno; Qamariah, Qamariah; Misbah, Misbah; Mahtari, Saiyidah; Rahman, Nor Farahwahidah Abdul (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Creativity has become a central objective in physics teacher education, yet it is often developed independently of responsibility, limiting the educational relevance and sustainability of students’ innovations. This study examined the potential of Project-Based Learning (PBL) to integrate creative responsibility with creative product development among pre-service physics teachers. Creative responsibility was conceptualized as the integration of creative engagement, reflective participation, collaboration, and awareness of the educational value and impact of project outcomes. A pre-experimental pretest–posttest design was implemented with two intact student groups participating in a series of collaborative project activities. Data were collected using a creative responsibility questionnaire and a rubric-based assessment of creative product development. The findings revealed consistent improvements in both creative responsibility and creative product development following the implementation of PBL, although the magnitude of improvement varied across the two groups. The most substantial progress was observed in students’ ability to design meaningful educational products, while creative responsibility also demonstrated positive development through collaborative inquiry, reflection, and iterative project refinement. These findings suggest that PBL provides a promising pedagogical framework for integrating creativity with responsibility, enabling pre-service physics teachers to generate innovative educational products while strengthening reflective, collaborative, and socially accountable professional competencies.